Is typing speed proportional to the severity of pain in keyboard workers with work-related upper limb disorder - Povlsen, Bo (Royal Society of Medicine Press, 2012)
OBJECTIVES: To investigate if typing speed is proportional to the severity of pain in keyboard workers with work-related upper limb disorder (WRULD). DESIGN: Standardized functional typing test with participants scoring pain before and after typing; calculation of typing speed. PARTICIPANTS: Fifty-nine patients and six controls. SETTING: Tertiary hospital centre for hand and upper limb pain. MAIN OUTCOME MEASURES: Pain (VAS 0–10) and calculation of typing speed as words per minute. RESULTS: Three subgroups of patients were found based on their typing speed: fast, slow and intermediate. Two-tailed student T-test with P level at 0.05 was used for evaluation. The typing speeds were significantly different between all three patient groups (P < 0.05). The typing speed was significantly faster in the fastest patient group than in the control group (P = 0.04) and the slow and middle groups (P = < 0.0001). The pain before typing was highest in the ‘slow’ group, in both hands but this difference was not statistically significant. CONCLUSION: Typing speed is not proportional to the severity of pain in keyboard workers with WRULD. Patients with statistically significant slower or faster typing speeds do not have statistically different levels of pain.